Dermoscopy of cutaneous and palmar lichen nitidus - Jayati Shailesh Dave; Sunanda Arun Mahajan; Prateek Oswal (Wolters Kluwer Medknow Publications, 2022)
Lichen nitidus (LN) is a relatively uncommon chronic cutaneous lichenoid group of disease characterized by tiny quintessentially discrete hypopigmented to skin coloured papules commonly seen over dorsa of hands/forearms, lower abdomen, penis, and buttocks. The cutaneous manifestation of a disease on palms/soles varies from their presentation on body, which makes it difficult to diagnose at times. A 23-year-old healthy female presented with mildly itchy lesions on bilateral wrist, fingers, elbows, peri-umbilical area, and left palm since 6 months. On dermoscopy, we could appreciate the classical described findings of LN which were confirmed on histopathology. LN has a characteristic dermoscopic features, which come to rescue for diagnosis and also avoid a biopsy. We describe a rare presentation of palmar LN with two different morphologies along with classical cutaneous distribution of LN and their dermoscopy.